Optimizing Technology-Based Social Entrepreneurship as a Driver of Inclusive Innovation in Urban Development Strategy - Winanda, Riski; Suherlan; Az Zaakiyyah, Hizbul Khootimah (PT. LITERASI SAINS NUSANTARA, 2025)
This study aims to examine the strategic role of technology-based social entrepreneurship in fostering inclusive innovation as part of an urban development strategy. Using a qualitative approach through a literature review method, this research analyzes 32 scholarly articles published between 2007 and 2025, selected from a total of 40 initial sources obtained through Google Scholar and credible websites. The analysis reveals that digital social entrepreneurship can serve as a catalyst for social transformation by creating solutions based on local needs, strengthening the socio-economic resilience of urban communities, and facilitating cross-sector collaboration. The study also identifies several challenges, including low technological literacy, limited digital infrastructure, and weak policy support. Referring to the theories of inclusive innovation, diffusion of innovation, and collaborative governance, this study affirms that optimizing technology-based social entrepreneurship requires a systemic approach involving the state, communities, and market actors to create a just and sustainable urban innovation ecosystem.